2021
DOI: 10.3389/fnins.2021.631311
|View full text |Cite
|
Sign up to set email alerts
|

Negative Modulation of the Metabotropic Glutamate Receptor Type 5 as a Potential Therapeutic Strategy in Obesity and Binge-Like Eating Behavior

Abstract: Graphical AbstractDiet-induced obese (DIO) C57BL/6 mice were treated for 14 days with VU0409106, a negative allosteric modulator of mGluR5. Food intake, body weight, inflammatory/hormonal levels, and behavioral tests were performed. Our data suggest reduction of feeding, body weight, and adipose tissue inflammation in DIO mice after chronic treatment with VU0409106.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…According to our data, mGluR5 did not present changes in IL-4/INF levels in mostly of the tested tissues. However, literatures shows that the negative modulation of mGluR5 by some drugs is able to decrease the transcription of NF-κB in T cell, TNFα, IL-12p70 and INFγ levels in EAT, which may reduce pro-inflammatory responses mediated by these cells 15 , 52 . Moreover, our data indicated that the absence of mGluR5 is associated to a higher IL-10/TNF ratio in the adipose tissue, which may indicate an anti-inflammatory tendency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our data, mGluR5 did not present changes in IL-4/INF levels in mostly of the tested tissues. However, literatures shows that the negative modulation of mGluR5 by some drugs is able to decrease the transcription of NF-κB in T cell, TNFα, IL-12p70 and INFγ levels in EAT, which may reduce pro-inflammatory responses mediated by these cells 15 , 52 . Moreover, our data indicated that the absence of mGluR5 is associated to a higher IL-10/TNF ratio in the adipose tissue, which may indicate an anti-inflammatory tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is found in the cells of innate and adaptive immunity, including macrophages, lymphocytes B and T 16 18 . Notably, some studies suggest that this receptor may contribute to fat deposition, metabolic dysfunction, and may also cause a systemic low grade chronic inflammatory state, especially in obesity 14 , 15 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we showed that the genetic deletion of mGluR5 in BACHD mice leads to a reduction in body weight. It has been reported that mGluR5 signaling is a mediator of appetite and energy balance 11,13 . Of note, a previous data showed that the blockade of mGluR5 may decrease anxiety behavior through serotonergic transmission, likely an increase in 5-HT release and the subsequent stimulation of 5-HT 2A/2C receptor 24 .…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, mGluR5 did not present changes in IL-4/INF levels in mostly of the tested tissues. However, literatures shows that the negative modulation of mGluR5 by some drugs is able to decrease the transcription of NF-κB in T cell, TNFα, IL-12p70 and INFγ levels in EAT, which may reduce pro-in ammatory responses mediated by these cells 13,50 . Moreover, our data indicated that the absence of mGluR5 is associated to a higher IL-10/TNF ratio in the adipose tissue, which may indicate an anti-in ammatory tendency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation